The Use of Interdisciplinary Approach in International Law Study in the Digital Era 5.0: Highlights and Future Research Directions - Tran, Thang Long (PRAWO i WIĘŹ, 2025)
International law faces numerous complex and novel challenges in the context of globalization and rapid technological advancements. This paper analyses the importance and potential of applying an interdisciplinary approach in international law research in the Digital Era 5.0. The results show that this method can enhance in-depth research on the relationship between international law and related fields, effectively address emerging legal challenges, improve the practicality of legal proposals, promote international cooperation in research, and enhance the ability to resolve international conflicts and disputes. The paper also identifies future research trends, including the application of artificial intelligence, blockchain, and other emerging technologies in international law research. The paper emphasises the development and refinement of interdisciplinary research methods to effectively respond to international legal challenges in the Digital Era 5.0.